Effect of land use systems on soil physical, chemical and biological properties in north-eastern region of India - MEENA, SIYARAM; MANJAIAH, K M; SHARMA, V K; BANA, R S; YADAV, SUNITA; MEENA, A R; SAINI, RAVI (The Indian Journal of Agricultural Sciences, 2025)
Soil plays a crucial role in crop production, and understanding its physiochemical properties across different land use systems (LUSs) is vital for developing effective land management strategies that enhance soil health. This study was carried out during 2022 and 2023 in the subtropical region of Tripura to assess the impact of various LUSs on the physical, chemical, and biological properties of soil. The study consisted of 12 LUSs, viz. T1, Oil palm (Elaeis spp.); T2, Litchi (Litchi chinesis); T3, Citrus; T4, Guava (Psidium guajava); T5, Rubber (Hevea brasiliensis); T6, Ginger (Zingiber officinale); T7, Uncultivated (A); T8, Rice (Oriyza sativa)-fallow; T9, Vegetable cowpea (Vigna unguiculata)-rice-maize (Zea mays); T10, Vegetable cowpea-rice-lentil (Lens culinaris); T11, Vegetable cowpea-rice-mustard (Brassica juncea); and T12, Uncultivated (B). The experiment was laid out in a completely randomized block (CRBD) design with three replications. Results showed that bulk density (BD) increased with depths, ranging from 1.15 Mg/m³ in litchi at 0–15 cm to 1.56 Mg/m³ in the uncultivated at 75–100 cm, indicating higher compaction in agricultural LUSs. Perennial crops like oil palm exhibited the highest mean nitrogen (340 kg/ha) and potassium (140 kg/ha) availability followed by litchi and rubber with notable reductions in pH values. Uncultivated LUS consistently recorded the lowest values with pH decreasing from 4.93 to 4.52 and nitrogen averaging 219 kg/ha. Mean soil organic carbon (SOC) content was highest in litchi (12.3 g/kg), rubber (11.8 g/kg) and oil palm (11.3 g/kg) and lowest in uncultivated A (5.29 g/kg). The SOC decreases with depths, with maximum values at 0–15 cm depth due to organic matter accumulation. Litchi exhibited the highest soil microbial biomass carbon (MBC 368.2 mg/kg) and nitrogen (MBN 82.1 mg/kg), followed by rubber, highlighting the role of perennial vegetation in promoting soil health compared to annual crops and uncultivated land. The study underscores the importance of horticultural land use systems, like litchi and rubber, in increasing SOC content, improving soil quality, and aiding climate change mitigation.